Au Nanoclusters Sensitized Black TiO2−x Nanotubes for Enhanced Photodynamic Therapy Driven by Near‐Infrared Light. Issue 48 (2nd November 2017) - Yang, Dan; Gulzar, Arif; Yang, Guixin; Gai, Shili; He, Fei; Dai, Yunlu; Zhong, Chongna; Yang, Piaoping
Abstract: The low reactive oxygen species production capability and the shallow tissue penetration of excited light (UV) are still two barriers in photodynamic therapy (PDT). Here, Au cluster anchored black anatase TiO2− x nanotubes (abbreviated as Au25 /B‐TiO2− x NTs) are synthesized by gaseous reduction of anatase TiO2 NTs and subsequent deposition of noble metal. The Au25 /B‐TiO2− x NTs with thickness of about 2 nm exhibit excellent PDT performance. The reduction process increased the density of Ti 3+ on the surface of TiO2, which effectively depresses the recombination of electron and hole. Furthermore, after modification of Au25 nanoclusters, the PDT efficiency is further enhanced owing to the changed electrical distribution in the composite, which forms a shallow potential well on the metal–TiO2 interface to further hamper the recombination of electron and hole. Especially, the reduction of anatase TiO2 can expend the light response range (UV) of TiO2 to the visible and even near infrared (NIR) light region with high tissue penetration depth. When excited by NIR light, the nanoplatform shows markedly improved therapeutic efficacy attributed to the photocatalytic synergistic effect, and promotes separation or restrained recombination of electron and hole, which is verified by experimental results in vitro and in vivo. Abstract : A novel nanoplatform with enhanced photodynamic therapy effect is first presented by decorating Au clusters on black anatase TiO2− x nanotubes. The nanoplatform shows markedly higher photodynamic activity and wider photoresponse range than pristine anatase TiO2 .